Two paradigms for divine healing : Fred F. Bosworth, Kenneth E. Hagin, Agnes Sanford, and Francis MacNutt in dialogue - Hejzlar, Pavel (Global Pentecostal and Charismatic studies, 2010)
Two distinct theologies of healing as represented by some of the foremost protagonists of the twentieth-century United States are analyzed and a solution is proposed to the tension generated by their differing approaches.